Оптимално управување со токови на енергија во микромрежи приклучени на дистрибутивната мрежа - Dimishkovska Krsteski, Natasha; Iliev, Atanas; Zenku, Imer (My University, 2022)
The increased penetration of renewable energy sources, as well as the higher standards for quality electricity, actualize the implementation of microgrids into the standard power system. Microgrids provide consumers with higher reliability of power supply, and characterize with lower costs and lower power losses. Microgrids consist of many different distributed generators, more interconnected consumers, batteries and backup generators, and therefore optimization is mandatory for proper and balanced operation of the microgrid. The paper analyses the problem of optimal energy management in a hybrid system (microgrid), which consists of a photovoltaic and wind generators, connected to the distribution network. Also, the microgrid includes industrial prosumers. An upgraded genetic algorithm is applied in the optimization, which takes into account the technical limitations of the installed equipment and the voltage levels in the nodes.
Keywords: Renewable energy sources, microgrid, genetic algorithm, optimization